PENERAPAN E-GOVERNMENT DALAM PELAYANAN PUBLIK DI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Yunita, Nur Ma’wa; Fatmawati, Fatmawati; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2025)
E-Government is an information technology system developed by the government to improve public services by providing choices to the public for convenience in public services. Based on this, this research study aims to describe and explain the Application of E-Government in Public Services in Mattiro Sompe District Pinrang Regency. This research uses a descriptive qualitative type using 6 informants. Data analysis techniques are data reduction, data presentation, data verification, and using triagulation data validation, namely source, technical and time triagulation. The results of this research show that the implementation of E-Government in Public Services in Mattiro Sompe District, Pinrang Regency has gone well, which can be seen from the E-SKM aspect in improving public services, Support has been effective in accordance with government policy in providing technological infrastructure, training and development Source human resources are qualified and competent, effective benefits in making it easier for the public to implement E-Government through filling out community satisfaction surveys and benefits for the government in improving services to the public.